Recovery of State Assets Through the Management of Assets Resulting From Criminal Acts With The Principle of Ongoing Concern: Maintaining The Sustainability of Asset Settlement - Soeherman Soeherman; Tuti Widyaningrum (IHSA Institute, 2026)
This study aims to analyze and construct the principle of Ongoing Concern in the legal context of asset management resulting from criminal acts, especially related to the Non-Conviction Based Asset Forfeiture mechanism in Indonesia. The Principle of Ongoing Concern, which is often used in the accounting and business worlds, was adapted in this study to see how the management of assets resulting from criminal acts can be carried out in a sustainable manner, even without criminalization. With a juridical-normative approach, this study analyzes existing regulations, laws and regulations related to asset confiscation and forfeiture, and challenges faced in the implementation of the Non-Conviction Based Asset Forfeiture mechanism in Indonesia. This research uses secondary data, obtained through a study of related legal literature, including books, journals, articles, and previous research. The results show that the application of the principle of Ongoing Concern in the management of assets resulting from criminal acts in Indonesia is still limited to the stage of confiscation and confiscation of assets, without clear guidelines for the interim management of confiscated assets. In addition, the institutions that manage assets resulting from criminal acts are not optimal, with a lack of coordination between law enforcement agencies and a lack of protection for the rights of third parties. This research formulates an ideal legal model that includes the establishment of an independent and professional asset management agency, cross-agency coordination procedures, and transparent audit and public reporting mechanisms. The resulting recommendations aim to create a more effective, accountable, and sustainable asset recovery system, with a focus on improving the technical capacity of law enforcement officials